Characteristics and patterns of International Students at Community Colleges: Lessons from the Open Doors Data (Comparative & International Education Series, 2021)
Chapter 3|18 pages Characteristics and Patterns of International Students at Community Colleges: Lessons from the Open Doors DataBy Julie BaerDrawing upon data from Open Doors®, this chapter highlights the characteristics and patterns of international student mobility to community colleges over the past fifty years.  It explores the growth in internationalization at community colleges beginning in the 1970s and describes how community colleges have welcomed international students from diverse locations worldwide.  The chapter provides statistical insights on the profile of international students at community colleges compared to national trends, such as international students’ place of origin, gender, marital status, enrollment status, primary funding source, and field of study.  The chapter concludes with a snapshot of how COVID-19 has impacted international student mobility in the United States based on IIE’s Fall 2020 International Student Enrollment Snapshot.